Potential impacts of general practitioners working in or alongside emergency departments in England: initial qualitative findings from a national mixed-methods evaluation. Issue 5 (24th May 2021) - Scantlebury, Arabella; Brant, Heather; Anderson, Helen; Leggett, Heather; Salisbury, Chris; Cowlishaw, Sean; Voss, Sarah; Benger, Jonathan Richard; Adamson, Joy
Abstract : Objectives: To explore the potential impacts of introducing General Practitioners into Emergency Departments (GPED) from the perspectives of service leaders, health professionals and patients. These 'expectations of impact' can be used to generate hypotheses that will inform future implementations and evaluations of GPED. Design: Qualitative study consisting of 228 semistructured interviews. Setting: 10 acute National Health Service (NHS) hospitals and the wider healthcare system in England. Interviews were undertaken face to face or via telephone. Data were analysed thematically. Participants: 124 health professionals and 94 patients and carers. 10 service leaders representing a range of national organisations and government departments across England (eg, NHS England and Department of Health) were also interviewed. Results: A range of GPED models are being implemented across the NHS due to different interpretations of national policy and variation in local context. This has resulted in stakeholders and organisations interpreting the aims of GPED differently and anticipating a range of potential impacts. Participants expected GPED to affect the following areas: ED performance indicators; patient outcome and experience; service access; staffing and workforce experience; and resources. Across these 'domains of influence', arguments for positive, negative and no effect of GPED were proposed. Conclusions: Evaluating whether GPED has been successful will be challenging. However, despite uncertainty surrounding the direction of effect, there was agreement across all stakeholder groups on the areas that GPED would influence. As a result, we propose eight domains of influence that will inform our subsequent mixed-methods evaluation of GPED. Trial registration number: ISRCTN51780222 .